Innovative activity in chosen branches of the tertiary sector in the Czech Republic - Eliska Jiraskova (International Journal of Business & Economic Development, 2015)
The aim of this paper is to provide a brief overview on innovation in services and their approach to the protection of intellectual property. The submitted article summarizes preparing part of a starting project mostly focused on investment environment. The area of interest is companies providing services in the territory of the Czech Republic. The aim of the project is supporting actions of promoting investment and innovative environment. It is necessary to exactly define innovation in services and to analyze innovative activity first so the aim could be achieved. A partial aim of the project will be finding out whether branches which report higher revenues from innovative activities are actively using the opportunity to patent their service because innovations are closely connected to the protection of intellectual property as well. The described part concerns innovations in selected branches of tertiary sector whereas all the branches which have been registered by Czech Statistical office, because of a validation of application for patent proceeding at least in two examined periods since 1993 are examined. Furthermore a possible dependency between an amount of patents in single regions and an amount of revenues coming from innovative companies to a region.